Theoretical foundations for teaching manual skills in health technologies. The case of histology technicians - Araoz, Rosa Alicia (2025)
Different technological specializations in health are dependent on operators who work under stress in order to optimize the final result, so training needs to include, in addition to skills, other knowledge that reduces uncertainty in students. Histotechnologists are characterized, among other functions, by the ability to cut, which evolved from the use of knives to mechanical systems, adding the concept of a tool to laboratory activity. For a long time, it was considered that after a manual skill was enhanced, that skill did not require voluntary action by the subjects, and was carried out automatically. In this work, we wish to show theories that offer a different way to organize and justify the technical teaching-learning process and how complex cognitive adjustments are produced that are far from simple automaticity. We will highlight the TLC (cognitive load theory) that was analyzed in different technological activities of hand-eye coordination.